JEJAK EMOSI DALAM RUANG KELAS STUDY LITERATUR TERHADAP PERAN KECERDASAN EMOSIONAL GURU DALAM PEMBELAJARAN - Maylida Syifaunnisa, Ajeng; S. Putra, Karantiano; Asri Pujiasti, Dea; Sunarti Cikal Putri, Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers’ emotional intelligence in the learning process through a literature review approach. Emotional intelligence is considered an important aspect that supports the effectiveness of learning because it influences classroom interactions, learning climate, student motivation, and classroom management. This research employed a qualitative descriptive method with a narrative literature review approach by analyzing various national and international journal articles related to teachers’ emotional intelligence in learning. The sources used were selected based on relevance, publication period, and scientific credibility. The findings indicate that teachers with good emotional intelligence are able to create a positive and inclusive classroom climate, build effective communication with students, increase students’ learning motivation, and manage conflicts and student behavior more wisely. In addition, teachers’ emotional intelligence also contributes to creating more humanistic, interactive, and effective learning processes. Therefore, emotional intelligence is not only a personal competence, but also an essential pedagogical competence that needs to be developed in educational practices and teacher professional development programs.